Extraction of phenolic compounds from Moringa oleifera Lam. leaves with ultrasonic-assisted deep eutectic solvents - Wang, Zilin; Tian, Yang; Yang, Min; Yang, Junyan; Wang, Yifan; Tao, Liang; Sheng, Jun; Shi, Chongying (Frontiers in Nutrition, 2024)
Background In this study, deep eutectic solvents (DESs) combined with ultrasound-assisted extraction (UAE) were used to extract bioactive compounds from the leaves of Moringa oleifera Lam. Methods The FT-IR method was used to analyze the structural characteristics of the DESs, and the extraction efficiencies of the DESs for total phenolic content (TPC) and total flavonoid content (TFC) were evaluated. The stability of the extracts under high temperature and UV radiation was assessed, and their antioxidant activity was investigated after undergoing in vitro simulated digestion. Results The results show that the seven DESs extracted more TPC and TFC than did the 70% ethanol (36.27 ± 1.58 mg GAE/g, 23.09 ± 1.47 mg RT/g), and the extraction process of UAE-DES was optimized by selecting choline chloride: citric acid as the DES solvent, which has the highest extraction of TPC (86.92 ± 1.34 mg GAE/g) and TFC (49.73 ± 0.85 mg RT/g). The stability results indicated that the DES phenolic extracts were less stable when exposed to high temperature and UV radiation, indicating that DES extracts have better bioactivity. Moreover, after in vitro simulated digestion, the DES extract shows a higher DPPH free radical scavenging capacity (12.79 ± 3.88 mmol Trolox/g of DES extracts, 6.99 ± 4.02 mmol Trolox/g of ethanol extracts) and ferric ion reducing antioxidant power (62.61 ± 1.71 mmol Trolox/g of DES extracts, 55.07 ± 1.66 mmol Trolox/g of ethanol extracts) than ethanol extracts. Conclusion This study confirmed that DESs are a new and environmentally friendly solvent that can be used for the extraction of phenolic compounds.